2022
DOI: 10.3389/fmolb.2022.982561
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and predictive values of serum metabolic profiles in sudden sensorineural hearing loss patients

Abstract: Sudden sensorineural hearing loss (SSNHL) is an otologic emergency, and metabolic disturbance is involved in its pathogenesis. This study recruited 20 SSNHL patients and 20 healthy controls (HCs) and collected their serum samples. Serum metabolites were detected by liquid chromatography-mass spectrometry, and metabolic profiles were analyzed. All patients were followed up for 3 months and categorized into recovery and non-recovery groups. The distinctive metabolites were assessed between two groups, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Metabolomics, reflecting both genetic traits and environmental influences, plays a crucial role in understanding various forms of hearing impairment [97]. Recent studies have reported consistent data on the predictive role of serum metabolic profiles in sudden hearing loss [98], noise-induced hearing loss [99], and the identification of markers for ototoxicity [97,100]. Metabolomic investigations may pave the way for improved diagnostic strategies, personalized interventions, and targeted treatments, ultimately enhancing the clinical management of individuals affected by different causes of hearing loss [101,102].…”
Section: Metabolomicsmentioning
confidence: 99%
“…Metabolomics, reflecting both genetic traits and environmental influences, plays a crucial role in understanding various forms of hearing impairment [97]. Recent studies have reported consistent data on the predictive role of serum metabolic profiles in sudden hearing loss [98], noise-induced hearing loss [99], and the identification of markers for ototoxicity [97,100]. Metabolomic investigations may pave the way for improved diagnostic strategies, personalized interventions, and targeted treatments, ultimately enhancing the clinical management of individuals affected by different causes of hearing loss [101,102].…”
Section: Metabolomicsmentioning
confidence: 99%
“…The main characteristics of the studies carried out in humans are summarized in Table 1. Of the 13 studies included, 8 were performed on urine samples [30][31][32][33][34][35][36][37]; 1 on perilymph [38], 2 on plasma [39,40] and 2 on serum [41,42]. The most commonly used technique for metabolomic profiling was liquid chromatography coupled with mass spectrometry (LC-MS); while only one study was performed by Nuclear Magnetic Resonance (NMR) and two by Gas Chromatography-Mass Spectrometry (GC-MS).…”
Section: Metabolomic Profiling In Humans With Hearing Lossmentioning
confidence: 99%
“…Wang et al [42] investigated sudden sensorineural hearing loss (SSNHL) and its metabolic implications. The research included 20 SSNHL patients and 20 healthy controls (HCs), with serum samples collected for analysis.…”
Section: Metabolomic Analysis On Blood-derived Samplesmentioning
confidence: 99%
See 2 more Smart Citations